ETNOBOTANI TUMBUHAN PANGAN MASYARAKAT DAYAK KANAYANT DI DESA BABANE KECAMATAN SAMALANTAN KABUPATEN BENGKAYANG KALIMANTAN BARAT - Megawati, Megawati; Wardoyo, Elvi Rusmiyanto Pancaning; Rafdinal, Rafdinal (Jurnal Protobiont, 2020)
Food plants is a human need to be met at all times. The pattern of utilization of plants in a society is closely related with their culture. Therefore, the culture of a region will determine the type of foods, the plant parts used, and  the way food is proceesed. The utilization of plants is important for the Dayak Kanayant  tribe especially in fulfilling food needs. The study is carried out for 3 months from June to August 2020.  The study aims to identify  the kinds of  food plants, and their use by Dayak Kanayant in Babane Village.  using the snowball method. The data obtained were analyzed descriptively. The results obtained  were 49 species of food plants,  from 31 families, and the most widely used families were moracaceae and aracaceae, 5 species in each of these families with a percentage of  10.20%. The  widely used  portion of the crop are  fruits with a percentage of  38.09%, while the location of food plants is found more in the forest with a percentage of 41.38%. the way to use it is generally consumed directly and some are processed by sauteed, boiled, burned, and fried.The methods of treating vegetation are boiled, dried in the sun, buried in the ground, added salt and sugar.